Caste or qualification? Chaitanya Vaishnava Discussions about Brahmanas in Colonial India - Martin Fárek (Theatrum Historiae)
Despite the general conviction about functioning of caste system in India we are far from understanding even its basic units, called varna and jati. If many scholars are not able to provide convincing solutions to problems with definition of caste and subcaste in India, it is necessary to anlayse the whole framework of thinking within which our modern discussions about caste developed. The general hypothesis of this article can be summarized in the following way: Discussions about caste system in India are constrained by Christian theological legacy within earlier Orientalist research. Nature of several problems we encounter in caste studies is discussed in the first part, before author develops critique of the dominant interpretation for rise of bhakti movements in Indian history. Although they are often described as protest against “caste system” in general and “brahmanical orthodoxy” in particular, relevant historical evidence shows very different picture. Chaitanya Vaishnava movement, very influential bhakti tradition during the British Raj, is a chosen example for analyses. Its resources provide us with domestic ideas and practices that are challenging dominant interpretations of both caste system and the rise and nature of bhakti movements themselves.